A política de economia solidária no ciclo orçamentário nacional (2004-2018): Inserç\~ao, expans\~ao e crise de paradigma - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This text aims to analyze the dynamics of the budget cycle (planning and execution process) of the solidarity economy policy in the federal government. For this purpose, a more general analysis was carried out on the strategic design of implementation and the operational evolution of the programs inserted in this theme, with the main focus being the budget execution potential of the respective administrative unit. The temporality of the analyzes covers all the recent experience of solidarity economy in the agenda of the federal government from the different Pluriannual Plans (PPAs) carried out during this period: 2004-2007, 2008-2011, 2012-2015 and 2016-2019. The results show that the programs developed for the implementation of the policy have undergone several problems that influenced the capacity to execute the actions and activities planned. Despite the maintenance of the thematic in the government agenda during all these years, everything indicates that the National Secretariat of Solidarity Economy (SENAES), an institutional locus of solidarity economy policy in the federal government, faces a moment of crisis as a paradigm of public policy in the field of work, which creates serious uncertainties about its continuity.
Keywords: H83; J23; 330; solidarity economy; social policies; budget cycle; state capabilities; government agenda